PO 141 - TO B OR NOT TO B – THE PERIOPERATIVE MANAGEMENT OF A PATIENT WITH HEMOPHILIA B UNDERGOING TOTAL KNEE ARTHROPLASTY - Pires, Vanessa; Sousa Dias, Carolina; Romão, Cristina; Antunes, Eva; Silva Pinto, José (Revista da Sociedade Portuguesa de Anestesiologia, 2023)
x